A New Complex Minimally Invasive Thread Lift Method for One-Time Three-Step Fixation of the Face and Neck Soft Tissues - Zhukova, Olga; Dydykin, Sergey; Kubíková, Eliska; Markova, Natalia; Vasil'ev, Yuriy; Kapitonova, Marina (Archives of Plastic Surgery, 2022)
Background In recent years thread lift has become widespread; however, existing methods need to improve their long-term outcome, which requires considering topographic anatomy of face and neck, especially the ligamentous apparatus. This study aims to assess the effectiveness and safety of an innovative method of one-time three-step thread facelift, which provides an additional support to the ligamentous structures of the upper, middle, and lower thirds of the face and neck.Methods The study included 357 patients aged 32 to 67 years with various morphotypes of aging. The original method of thread lift was applied, and its effectiveness was followed up for to 2 years. The Wrinkle Severity Rating Score (WSRS) and Global Aesthetic Improvement Scale (GAIS) scores were used for assessment by investigators, independent observers, and patients. Statistical significance was determined using paired t-test and chi-square test.Results The mean WSRS score was 3.88 ± 0.88 before the thread lift, 1.93 ± 0.81 one month after the procedure, and 2.36 ± 0.85 after 2 years of follow-up. The mean GAIS was 4.80 ± 0.04 one month after thread lift, and 4.01 ± 0.04 after 2 years, while in the patients' assessment Global Satisfaction Scale was 4.86 ± 0.02 and 4.10 ± 0.02, respectively. There were no clinically significant complications throughout the observation period.Conclusion The new method of one-time three-step thread fixation of the soft tissues of the face and neck demonstrated a high degree of satisfaction by both experts and patients after 2 years of follow-up. It showed high efficacy and safety, including in the group of patients with pronounced age-related changes of the skin of face and neck.
Keywords: aesthetic; face; minimally invasive facial lifting procedures